The Role Of Healthcare Support Workers In Providing Palliative And End-Of-Life Care In The Community At Saudi Arabia:A Systematic Review 2024 (The Review of Diabetic Studies, 2024)
Background Despite the widespread use of Health Care Support Workers (HCSWs) in providing palliative and end-of-life care, there is little information available about their contributions towards supporting patients who want to be cared for at home or to die at home. Informal caregivers are the backbone of home-based palliative care (PC) because they play a vital role in offering more seamless and timely support, preventing suffering and fostering comfort and dignity. Specialized home-based PC teams must recognize unmet needs in fulfilling daily responsibilities and enhance their preparedness for caring.  (a) explore how PC professionals perceive the preparedness of ICs to provide PC at home and (b) determine what barriers and enablers they consider essential for the delivery of high-quality PC at home. Globally, the demand for community palliative care, delivered within the home setting, is rising. Hospice support workers, also referred to as healthcare assistants, play a crucial role in providing this care, but evidence indicates they face challenges relating to inadequate training, isolation and emotional labor.Aim of this systematically review: To evaluated the role of healthcare support workers in providing palliative care in the community at Saudi Arabia 2024.Method:  the review was conducted in two databases (Scopus and PubMed) with the use of the following keywords: “Role of Health Care support workers and palliative  care”, “providing palliative  care in the community ”, “social issues,“ demographic profiles ” , from September 2024 to January 2024.who worked in specialized PC teams were recruited for a descriptive qualitative research study. Results: The findings that appeared to be about the same topic grouped together. Grouping findings according to their topical similarities allowed us to recognize whether the findings from different studies confirmed extended or refuted one another. This helped preserve the integrity and complexity of the finding, thus optimising the validity of the integration process.Conclusion: Professionals deemed it essential for healthcare support PC staff to be experienced, accessible, person-centered, and proactive. Furthermore, effective communication and a well-defined network for requesting certain community resources or services were deemed crucial for delivering high-quality PC at community